Avaliação do efeito de piraclostrobina aplicada ao final do perfilhamento sobre a produtividade da cultura do trigo (Triticum aestivum) - Trojan, Daiane Garabeli (2009)
The fungicide from the group of the strobilurin promote physiologies changes wich allow, positive events reflected on productivity in way of growth, aiming to estimate the alteration effects in the plant’s physiology, about the incomes and the control of the main illnesses in diferent wheat variety, to the conditions of Campos Gerais, this paper was developed. The experiment was achieved in Ponta Grossa-PR, winter’s harvest 2008, with the variety OR-1, CD-104, SUPERA, SAFIRA, CD-113, BRS-208 and AVANT, containing 26 treatments distributed in 4 randomized blocks. The program ME was estimated in 4 diferent doses, while to the illnesses handling were estimated the diferent fungicides combinations in three sprayings. The treatments were: absolute witness (T1); pyraclostrobin on doses of 250,0; 125,0; 93,75 e 62,5 g i.a ha applied only in the end of the tillering (T2; T3; T4 e T5); pyraclostrobin + epoxiconazole - 133 + 50 g i.a ha, with 3 applications starting from the stem extension and the addition of the Program ME on doses of 0; 62,5; 93,75 125,0 and 250,0 g i.a ha-1, (T6; T7; T8; T9 e T10 , respectively); pyraclostrobin epoxiconazole - 260 + 160 g i.a ha (T11; T12; T13; T14 e T15); pyraclostrobin +metconazole - 150 + 80 g i.a ha-1, (T16; T17; T18; T19 e T20), axozistrobina+ ciproconazole - 60 + 24 g i.a. ha-1 and tefluzostrobin+tebuconazole - 60 + 120 g i.a ha-1(T21; T22; T23; T24, T25 e T26). Valuations were achieved to the blight and leves stain control during the culture develop, with illnesses valuations starting from the leves flag e flag-1 (useful area of the piece 3,4m2). According to the results it was checked that with the Program ME application there was a reduction in the illnesses’ severity and growth in the productivity, confirming the positive effect from this program on the wheat culture.